2017
DOI: 10.1002/adsc.201700278
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Vicinal Difunctionalization of Alkynes through a Three‐Component Reaction of Alkynes, Sodium Sulfinates, and Togni Reagent

Abstract: Stereoselective vicinal difunctionalization of alkynes through trifluoromethylation and sulfonylation via a three‐component reaction of alkynes, sodium sulfinates, and Togni reagent under catalyst‐ and additive‐free conditions has been realized. This reaction proceeds at room temperature in dimethyl sulfoxide (DMSO), providing (E)‐β‐trifluoromethylvinyl sulfones in moderate to good yields. The advantages of this tandem radical process include extremely mild conditions, excellent stereoselectivity, and easy exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 95 publications
0
10
0
1
Order By: Relevance
“…Among those, radical-involved vicinal difunctionalization of alkynes by a sulfone radical represents as a powerful method for building polysubstituted vinyl sulfones via a one-step operation (Scheme ). Examples are halosulfonation, hydrosulfonation, selenosulfonation, aminosulfonylation, phenoxysulfonylation, and carbosulfonylation . Despite these advances, the development of an efficient path for synthesizing thio-substituted vinyl sulfone scaffold remains elusive (Scheme ).…”
mentioning
confidence: 99%
“…Among those, radical-involved vicinal difunctionalization of alkynes by a sulfone radical represents as a powerful method for building polysubstituted vinyl sulfones via a one-step operation (Scheme ). Examples are halosulfonation, hydrosulfonation, selenosulfonation, aminosulfonylation, phenoxysulfonylation, and carbosulfonylation . Despite these advances, the development of an efficient path for synthesizing thio-substituted vinyl sulfone scaffold remains elusive (Scheme ).…”
mentioning
confidence: 99%
“…A wide range of ( E )-β-trifluoro-methyl vinyl sulfones were obtained in moderate to good yields with excellent stereoselectivity by using various terminal alkynes, different benzenesulfinates, heteroarenesulfinate or alkanesulfinates and Togni reagent ( Scheme 235 ). 343 The internal alkyne, phenylpropyne, was employed for the synthesis of tetrasubstituted vinylsulfones in low yield with excellent stereoselectivity.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…In 2017, the Wu group reported the stereoselective preparation of (E)-β-trifluoromethylvinyl sulfones 86 via the vicinal difunctionalization of alkynes with sodium sulfinates 85 and Togni's reagent 2 (Scheme 18). 27 This transformation features a wide reaction scope and good functional-group tolerance. The results of mechanistic studies indicated that a SET process taking place between Togni's reagent 2 and sodium sulfonates 85 would produce a CF 3 radical and the sulfonyl radical 88.…”
Section: Lewis Base Catalytic Systemsmentioning
confidence: 99%